M30 Effect of dose reductions and/or interruptions on the efficacy of nintedanib in patients with idiopathic pulmonary fibrosis (ipf): subgroup analysis of the inpulsis trials. (15th November 2017) - Maher, TM; Inoue, Y; Case, AH; Sakamoto, W; Stowasser, S; Wuyts, WA
Abstract : Introduction and Aim: The efficacy and safety of nintedanib in patients with IPF were assessed in two replicate Phase III placebo-controlled INPULSIS trials. In both trials, nintedanib reduced disease progression by reducing decline in FVC. The recommended dose of nintedanib was 150 mg bid, but dose reductions to 100 mg bid and treatment interruptions were allowed for the management of adverse events. Following dose reduction, the dose could be re-escalated to 150 mg bid. We assessed whether dose reductions and/or treatment interruptions influenced the effect of nintedanib on reducing FVC decline. Methods: We assessed change from baseline in FVC (mL) at week 52 in subgroups of patients by their last dose (150 mg bid or 100 mg bid) and whether they had experienced a dose reduction and/or treatment interruption using pooled data from both INPULSIS trials. Patients who prematurely discontinued trial medication but had an FVC value at week 52 were included in the analysis. Analyses were descriptive and based on observed cases. Results: A total of 864 patients were included in the analysis (519 treated with nintedanib, 345 with placebo). Most (75%) patients did not have a dose reduction or treatment interruption. Mean (SD) changes from baseline in FVC at week 52 in subgroups by dose are shown in the Table. In patients who took nintedanib 150 mg bid as their last dose, absolute mean changes from baseline in FVC at week 52 were −118 mL and −90 mL in patients who did and did not have any prior dose reduction and/or treatment interruption, respectively. In patients who took nintedanib 100 mg bid as their last dose, mean change from baseline in FVC at week 52 was −74 mL. These changes were consistent with the decline in FVC observed in the whole nintedanib group (−89 mL). Conclusion: Pooled data from the INPULSIS trials show that decline in FVC was similar in patients treated with nintedanib irrespective of whether they had dose reductions and/or treatment interruptions. These Results suggest that the dosing regimen used in the INPULSIS trials was effective at reducing disease progression in patients with IPF. Please refer to page A261 for declarations of interest in relation to abstract M30.